Development and Validity of the Fear of Water Assessment Questionnaire - Misimi, Fatmir; Kajtna, Tanja; Misimi, Samir; Kapus, Jernej (Frontiers in Psychology, 2020)
Fear of water is the strongest predictor for no or low swimming competencies. Some individuals will never learn to swim due to their complete avoidance of water, whereas others might have difficulty with learning due to the fact that they cannot sufficiently relax their body to facilitate floating or swimming. Therefore, it is important to identify these people and to establish effective teaching strategies that can best help this specific population. Recognizing this, there is a clear need for an assessment tool which can help swim teachers and coaches identify people with a fear of water. The study aimed to first develop and then validate a fear of water assessment questionnaire (FWAQ). 2074 male and female people participated in the creation of a 40-item questionnaire. The exploratory factor showed that a 3 factor solution including 20 items was most sensible – such a solution accounted for 31.69% of explained variance and the Cronbach’s alpha α was 0.831, which makes for a reliable enough solution. A subsequent discriminant function analysis correctly classified 98.2% of participants. We concluded that the findings from this study support that the FWAQ is a valid scale that effectively identify people with fear of water.